Finerenone in type 2 diabetes and renal outcomes: A random-effects model meta-analysis - Ghosal, Samit; Sinha, Binayak (Frontiers in Endocrinology, 2023)
Background: The nonsteroidal mineralocorticoid antagonist finerenone is a new addition to the list of agents (angiotensin converting enzyme inhibitors and sodium glucose cotransporter 2 inhibitors) conferring renal protection to patients with diabetic kidney disease. Two recent meta-analyses using the fixed effect model in patients with chronic kidney disease (both diabetic and nondiabetic populations) came to a conflicting conclusion on the effect of finerenone on eGFR decline. This meta-analysis was undertaken exclusively in the type 2 diabetes (T2D) population to explore the robustness and heterogeneity of the effect size by conducting a random effects model meta-analysis along with draft plots and prediction intervals. Materials and methods: A database search was conducted using the Cochrane library to identify relevant citations. Analysis was conducted using RevMan 5.4.1 and R studio RStudio. (2022.07.1, Build 554). The hazard ratio was used as the effect size for the renal composite, while the standardized mean difference (SMD) was used to estimate the effect size of eGFR decline and reduction in the urine albumin creatinine ratio (UACR). Results: A pooled population of 13,943 patients from four citations was included for analysis. The Cochrane risk of bias was used to assess the quality of the studies. There was a significant 16% reduction in the renal composite (kidney failure, a sustained decrease of at least 40% in the eGFR from baseline, or death from renal causes) [HR: 0.84, 95% CI 0.77-0.92, 2: 0, I2: 0%). Finerenone was also associated with reduction in UACR (SMD: -0.49, 95% CI -0.53 to -0.46, 2: < 0.0001, I2: 0%, prediction interval: -0.57 to -0.41) and prevention of decline in eGFR (SMD: -0.32, 95% CI -0.37 to -0.27, 2: < 0.0001, I2: 0%, prediction interval: -0.43 to -0.21) without any evidence for significant heterogeneity. Except for an increase in hyperkalaemia (RR: 2.22, 95% CI 1.93-2.24), adverse events were observed with fineronone compared to placebo (RR: 1.00, 95% CI 0.98-1.01). Conclusion: There are significant benefits in renal outcomes associated with finerenone treatment in T2D patients with established chronic kidney disease with a side effect profile comparable to placebo.